ln(y)=ln(x+C)

Simple and best practice solution for ln(y)=ln(x+C) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(y)=ln(x+C) equation:


Simplifying
ln(y) = ln(x + C)

Multiply ln * y
lny = ln(x + C)

Reorder the terms:
lny = ln(C + x)
lny = (C * ln + x * ln)
lny = (lnC + lnx)

Solving
lny = lnC + lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1lnC' to each side of the equation.
-1lnC + lny = lnC + -1lnC + lnx

Combine like terms: lnC + -1lnC = 0
-1lnC + lny = 0 + lnx
-1lnC + lny = lnx

Add '-1lnx' to each side of the equation.
-1lnC + -1lnx + lny = lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
-1lnC + -1lnx + lny = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-1C + -1x + y) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-1C + -1x + y)' equal to zero and attempt to solve: Simplifying -1C + -1x + y = 0 Solving -1C + -1x + y = 0 Move all terms containing l to the left, all other terms to the right. Add 'C' to each side of the equation. -1C + -1x + C + y = 0 + C Reorder the terms: -1C + C + -1x + y = 0 + C Combine like terms: -1C + C = 0 0 + -1x + y = 0 + C -1x + y = 0 + C Remove the zero: -1x + y = C Add 'x' to each side of the equation. -1x + x + y = C + x Combine like terms: -1x + x = 0 0 + y = C + x y = C + x Add '-1y' to each side of the equation. y + -1y = C + x + -1y Combine like terms: y + -1y = 0 0 = C + x + -1y Simplifying 0 = C + x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -2x-23=-19 | | Y^2+3y=4y-6 | | 8(r+7)=88 | | 2n-(14-n)=1 | | 10s^2+23s-42=0 | | 18(3.24)=3.24+0.99s | | Y^2+3=4y-6 | | 1+2b-8b=7 | | x+8=-(8-x) | | 9j+3=30 | | 5z^2-18z-8= | | 4x+10+6x-8=9x+5 | | h(t)=-5t^2+20t-15 | | 13=v-3 | | 6(x-3)=2(3x+2) | | 5y-3=-6+8y | | 17.5y+19.28-0.2y=3.92+16.1y | | 1(4-x)=-14 | | -21=n/3+5 | | 4z^2-23z+15= | | 170+180=m+32+m | | 2z^2+13z+21= | | 1.75=-.25+w | | 2x-18+3x+12=13x-30 | | 4-1(3h+2)=1-1(5-7h) | | (15*2)+(w*2)=50 | | 20a^2+16a^3= | | .20x=30 | | 2v-8=3v+5 | | 4(2x+4)=10x+15+1 | | 9y^2-13y^3= | | -5x+y=15 |

Equations solver categories